A Conceptual Model of Perceived Social Support, Maqasid Syariah Quality of Life and Health Status - Mahadzirah, Mohamad; Nor Azman, Mat Ali @ Salim; Harmy, Mohamed Yusoff; Fazida, Karim (2015)
The criminal offence of most inmates in prison is related to drug abuse. Drug abuse inmates experienced higher health problems than the general public. It was reported that factors such as social support and quality of life could influence the improvement of health status among drug abuser while they were imprisonment. Previous studies suggested that there were positive relationships among perceived social support, quality of life and health status. However, these studies did not extensively examine the relationships of these constructs among drug abuse inmates. Therefore, this study proposed a model that examined the relationships of these constructs among drug abuse inmates. In addition, this study proposed the use of the Maqasid Syariah approach to measure quality of life, which has never been examined in the previous studies. The main objective of this study is to propose and validate a conceptual model that examines the relationship among social support, quality of life and health status among drug abuse inmates. Self-administered questionnaires will be distributed to drug abuse inmates at several identified prisons in Malaysia using area sampling approach. The selection of the respondents will be conducted using systematic sampling method. Structural equation modeling will be used to validate the proposed model. This study expects to discover a positive relationship between social support and health status. Besides that, quality of life plays the role of mediating variable in the relationship between social support and health status among drug abuse inmates. The findings of the study provide insightful information pertaining to several aspects of social support and I-QoL that would improve the drug abuse inmates’ health status.